Nanoengineering of Chitosan Sponges Via Atomic Layer Deposition of ZnO for Water Remediation Technologies - Sara Lotito; Domenico Cignolo; Jennifer Gubitosa; Gianni Barucca; Paolo Mengucci; Marinella Striccoli; Fabio Palumbo; Pinalysa Cosma; Paola Fini; Sapia Murgolo; Vito Rizzi; Francesco Fracassi; et al. (Advanced Materials Interfaces)
Abstract Low‐cost, millimeter‐thick chitosan‐based sponges are engineered with zinc oxide (ZnO) using atomic layer deposition (ALD) to create a multifunctional nanocomposite for the potential application in water remediation and self‐regeneration via solid‐state photocatalysis. Initially, non‐porous chitosan films served as control samples to study the ZnO growth mechanism and its impact on the biopolymer's optical and chemical properties. Subsequently, porous chitosan sponges are engineered to further explore the photocatalyst growth and infiltration into the porous matrix. The characterization of the chitosan/ZnO hybrid material is performed using spectroscopic ellipsometry, X‐ray photoelectron spectroscopy, UV–vis, photoluminescence, and infrared spectroscopy, analyzing the effect of varying the number of ALD cycles, resulting in different ZnO thicknesses in the range of 5–30 nm on the chitosan matrix. A reaction‐limited growth model is found and strong interactions between ZnO and chitosan amino groups significantly enhance the stability in water and impart photocatalytic features. Adsorption tests using Direct Blue 78 dye demonstrated high removal efficiency, with capacities up to 2000 mg g−1, surpassing pristine chitosan sponges, which degrade in water. Electrostatic interactions between dye sulfonate groups and protonated chitosan amino moieties are identified as key to this performance. Preliminary photocatalytic experiments using Naproxen confirms the ZnO‐coated sponges' ability to degrade pollutants, showcasing ALD as a key technology for producing bio‐based, photoactive materials for sustainable water treatment.